Animações interativas como instrumento pedagógico nas aulas experimentais de física : a concepção dos professores - Ribeiro, Tiago Nery (2009)
The integration of Information Communication Technology in schools is a process that has already started, and that tend to change sooner or later, the profile of the teaching-learning process. The animation software can become an alternative to streamline the process of teaching and learning of physics, making it more meaningful for the student. Therefore, this study aimed to examine the concepts of physics teachers in high school about the software of animation as a pedagogical tool in the classroom and provide opportunities for learning. For this, we established a theoretical framework on the evaluation criteria and definition of software for animation as a pedagogical tool, know the difficulties that teachers of physics are in the process of teaching-learning software transformations characterize the thermodynamic analysis prior to the teachers and analyze the conceptions of the same software on the animation. Then, we established a theoretical framework on the evaluation criteria and definition of software for animation as a pedagogical tool, know the difficulties that teachers of physics are in the process of teaching-learning software transformations characterize the thermodynamic analysis prior to the teachers and analyze the conceptions of the same software on the animation. For this purpose, as a theoretical contribution to the meaningful learning theory of David Ausubel. For the development of the research we used a qualitative methodology using a semi-structured interview. Accordingly, from the theoretical framework and concepts of the teachers can see that one of the main characteristics of software as a tool for teaching animation classes in experimental physics is how it can facilitate the process of teaching learning and the student must construct the their knowledge of the theoretical and experimental, between the static and dynamic. We also show that the conceptions of teachers could validate the set of criteria defined in the theoretical framework that are predominant in the learning process with this type of tool, which are the basis used in the construction of educational software and the technical aspects.